The Correlation of Volume Overload Measured by Bio Impedance Analysis and Intradialytic Hypertension in End Stage Kidney Disease Patients at Bandung Hasan Sadikin Hospital - Iqbal, Muhammad; Bandiara, Ria; Supriyadi, Rudi; Dwipa, Lazuardhi (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Abstract Background: Assessing dry weight is essential for calculating the ultrafiltration volume during dialysis. Volume overload affects hemodynamic stability including intradialytic hypertension (IDH). Using Bio Impedance Analysis (BIA) to guide fluid assessment enhances the accuracy of fluid overload evaluation. Objective: Find the correlation between volume overload and IDH in patients undergoing chronic dialysis at Bandung Hasan Sadikin Hospital. Methods: This is a cross-sectional study to evaluate the correlation of volume overload and IDH in patients undergoing chronic dialysis at Bandung Hasan Sadikin Hospital. Exclusion criteria was patient below the age of 18 years old, unable to performed BIA measurement. Blood pressure before, during and after dialysis session was recorded to asses IDH. BIA was measured after dialysis session. Point biserial correlation used to analyze correlation between volume overload and intradialytic hypertension. The data were analysed with SPSS version 23.0. The statistical significance was set at P<0.05. Result: Ninety-seven patients enrolled, the average age was 49,9 ± 12.3 years old, 55,7% was male. There were 23,7% of patients with IDH with increasing systolic blood pressure of 19.21 mmHg (10-66). A significant correlation was observed between the incidence of IDH and the percentage of volume overload after dialysis with R coefficient 0,238 (p 0,014). Conclusion: The majority (59.87%) of patients undergoing chronic hemodialysis had a greater dry weight based on BIA examination, 23,7% had IDH and its occurrence has a significant correlation with the percentage of volume overload after dialysis. Keywords: volume overload, dry weight, BIA, IDH.